The Canadian Agreement on Internal Trade : Developments and Prospects - Leidy, Michael (IMF Working Papers; Working Paper, 1998)
Under a federal system of government, the division of responsibilities between the federal, provincial/state, and local levels of government may create internal barriers to trade. To deal with this problem, the federal and provincial governments in Canada established the Agreement on Internal Trade (AIT). This paper takes stock of the achievements and shortcomings of the AIT. Because the internal barriers to trade being addressed by the AIT are not unique to Canada, the agreement presents a useful model for reform that could be emulated by other countries.